The revolution in systems engineering. - Hellestrand, G.R.
The process of engineering systems on a chip will transform relationships among hardware, software, and mechanical designers. Various issues in systems engineering are discussed as is the role of systems engineering as a process. Co-design objectives and the state of co-design in electronic design automation are then considered as are virtual system prototypes
Keywords: Co-design objectives; Electronic design automation; Hardware design; Mechanical design; Software design; Systems engineering; Virtual system prototypes